To Study the Revolutionary Intellectuals in Cuba and Chile During the Socialist Construction. A Proposal of Connected Intellectual History - Lozoya Lopez, Ivette (Revista de Historia Social y de las Mentalidades, 2024)
The following article presents a theoretical-methodological reflection regarding the study of left-wing intellectuals in socialist construction in Chile and Cuba between 1959 and 1973. This view contributes to elucidating the challenges posed by analysing the subjects' trajectories and the phenomena linked to political thought and culture in two processes self-defined as revolutionary built from different strategies. Thus, new analytical perspectives open up for the epistemic field of left-wing intellectual history in Latin America between 1960 and 1970 from the methodological, theoretical frameworks of intellectual history and connected history.
Keywords: Intellectuals; Revolutionary; Socialism; Cuba; Chile